THE ROLE OF LOCAL REGULATIONS IN HANDLING DOMESTIC VIOLENCE (KDRT) - Supian Ramli; Sulaiman Sulaiman; Endang Wahyuni (Adisam Publisher, 2025)
This research aims to evaluate the role and effectiveness of local regulations in handling domestic violence cases. The method used is a literature review. This study identified that the existence of regional regulations is very important as a legal umbrella to protect victims and provide sanctions for perpetrators of domestic violence. However, the effectiveness of local regulations is still questionable given various challenges, including the capacity of law enforcement officers, inadequate resources and infrastructure, and lack of supervision in their implementation. The results show that while local regulations have been a progressive step in addressing domestic violence, their role is often limited to the normative level and lacking in effective concrete actions. Factors such as unawareness or low knowledge of domestic violence among law enforcement officials and the community, strong social stigma, and a non-integrated referral and victim assistance system, further hinder the implementation of this policy. Therefore, a multi-sectoral approach involving cooperation across institutions and sectors of society is needed to improve the effectiveness of this regional regulation. Capacity building for law enforcers, improved support facilities for victims, intensive socialization, and systematic monitoring and evaluation strategies are needed to ensure that the regional regulation can contribute significantly to reducing domestic violence and effectively protect victims' rights.